2014-11-25T19:44:31+08:00
How to get inverse function:
Step 1. Change x to f(x) or x to f(x) and vice versa.
Step 2. You will need to derive the function to have f(x) or y in the other side again.

If it is indeed f(x) = 4/x + 2, then the inverse function will be f(x) = 4/(x-2).
Solution:  Let the "f(x)" be "y" here,
x = 4/y+2
x-2 = 4/y
(x-2)/4 = 1/y
4/(x-2) = y therefore the inverse of f(x) 4/x + 2 is f(x) = 4/(x-2).

However, if it is merely a typographical error and intended to be f(x) = 4/(x+2), then the inverse of the function will be f(x) = 4/x - 2
Solution: Let the "f(x)" be "y" here.
x = 4/(y+2)
y+2 = 4/x
y = 4/x - 2 therefore the inverse of f(x) = 4(x+2) is f(x) = 4/x - 2
Thank you so much
<3 You're welcome
2014-11-25T20:31:35+08:00

Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
Inverse function means changing x to y
f(x)=4/(x+2)
y=4/(x+2)
x=4/(y+2)
x(y+2)=4
xy+2x=4
xy=4-2x
y=(4-2x)/x
x≠0

Hope this helps =)
Thank you :)
np =)